The Correlation Between Knowledge and Behavior in Antibiotic Use in Martapura District - Herningtyas Nautika Lingga; Difa Intannia; Muhammad Rizaldi (Lambung Mangkurat University, 2025)
Irrational use of antibiotics can cause various negative impacts on health, one of negative impacts is the occurrence of antibiotic resistance. Good knowledge of antibiotics is needed by individuals because it is one of the factors that can affect the behavior of using antibiotics. This study aimed to determine the relationship between knowledge and behavior in the use of antibiotics in the people of Martapura District. This study was a descriptive study with a cross sectional design with 110 people in Martapura District as respondents who have used antibiotics. The instrument used was a questionnaire that has been tested for validity and reliability. Data analysis was performed using Rank Spearman correlation test. The results showed that majority of respondents were female (66,36%) with an age range of 38-47 years (30,91%), the last education was SMA/SMK (47,27%) and a job as a housewife (37,37%). The average score of the knowledge of the people of Martapura District about antibiotics was 7,11 ± 1,69 and the average score of behavior was 6,55 ± 2,45. The concluded from the correlation test results obtained a p value of 0,307, which means that there was no relationship between knowledge and behavior in using antibiotics in the people of Martapura District.